REKALKULASI TRANSFORMASI KELOMPOK PENEKAN MENJADI PARTAI POLITIK: KAJIAN PADA HIZBUT TAHRIR INDONESIA - Zainuddin, M.; ', Suryaningsih (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
The article to analyzes the opportunities Hizbut Tahrir Indonesia for transform of pressure groupinto a political party. This study stems from the analysis of a pressure group or organization thathas been in Indonesia and ever tried to transform itself into a political party. This study took morecases in Pekanbaru. The results of the analysis of the strengths and opportunities describe HizbutTahrir Indonesia and predicting his desire to become a political party contestants elections inIndonesia in the future. The results of this study found a new theory about the transformation of apressure group into a political party. Hizbut Tahrir Indonesia has conducted political movementsfrom the beginning until now. Ideals end of Hizbut Tahrir Indonesia is to establish the KhilafahIslamiyah. In the concept of a single -party system, then the Khilafah Islamiyah may be referredto as having a single-party system in the party system of a country.